METHODS OF SMALL CAPACITANCE MEASUREMENT IN ELECTRICAL CAPACITANCE TOMOGRAPHY - Smolik, Waldemar; Kryszyn, Jacek; Olszewski, Tomasz; Szabatin , Roman (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
The paper presents the main methods of small capacitance measurement used in electrical capacitance tomography: the AC method with a sine wave excitation and the charge-discharge method with square wave excitation. Construction of synchronous detector for both circuits was discussed. A modified "charge-discharge" method was presented.